PRINCIPLE OF POINT MAKING OF MULTI-PROJECTION DECISION - Olga N. Lapaeva (Статистика и экономика, 2016)
The principle of point making of multi-projection decision in economics is setforth in the article. The principle envisagessearching for the best variant in eachprojection and result making by crossingof partial sets.